Caitlin Macfarlane (Author): Gender Displaced: Are the Rights of Female Syrian Refugees Protected in Jordan? - Bendel, Petra (FAU University Press, 2018)
This study aims to provide an overview of the human rights protections in place for Syrian refugee women and girls in urban and rural Jordan, as well as in-camp settings. The paper outlines the gaps in protection available and accessible for this group, as well as specific focus areas in need of attention: sexual and gender-based violence (SGBV), including early marriage; the changing role of women in the face of displacement, and women’s access to gender-related healthcare. Whilst understanding there are other variables to the full enjoyment of human rights, this paper looks at the international, national and local efforts in place to provide protection for Syrian refugee women and girls in Jordan, and concludes with recommendations to better provide basic yet essential human rights protection
Keywords: Syria; human rights protection; gender; Jordan; refugee women